Kepuasan Konsumen Terhadap Atribut Produk Ikan Kaleng Merek ABC di Pasar Bung Karno Kecamatan Baturetno - Bilqisti Alya Khoirunnisa; Rosita Dewati; Agung Setyarini (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2024)
Indonesia is a maritime country, but the distribution of the marine fisheries has not been evenly distributed to overcome this issue.  It is necessary to diversify food through agro-industrial fisheries, such as canned fish products. The research aims to analyze the importance and customer satisfaction of the attributes of ABC canned fish brand in Bung Karno Market, Baturetno District, Wonogiri Regency. The basic method of research is descriptive analysis with a quantitative approach. The method of determining the location and the sample are using purposive sampling that is Bung Karno Market, Baturetno District, Wonogiri Regency. As many as 96 respondents with criteria have bought  at least 1 ABC canned fish at Bung Karno Market, Baturetno Regency. The data analysis method used Importance Performance Analysis and Customer Satisfaction Index. The result of the Importance Performance analysis method showed that in quadrant I (concentrate here), there are attributes of price and number of fish inside the can. Quadrant II (keep up the good work): there are attributes of the taste and the ease of opening the can. Quadrant III (low priority) contains color sauce and sauce viscosity attributes. Quadrant IV (possible overkill) contains attributes of aroma. The result of the Customer Satisfaction Index analysis showed that the level of customer satisfaction towards all of the attributes of ABC canned fish products is 79.06%, which is included in the satisfied category